Urban Aboriginal Health: Issues, Culturally Appropriate Solutions and the Embodiment of Self-Determination - Skye, Jairus S. (My University, 2013)
Urban Aboriginal health and health-related issues are steeped within the sociohistorical, sociocultural, and sociopolitical experiences of Aboriginal peoples since European contact. Thus, urban Aboriginal health issues are very complex in that they consist of aspects associated with collective as well as individual cultural and political life experiences. Therefore, in order to adequately address Aboriginal health issues a comprehensive and multidisciplinary approach is required.
This study examines how Anishnawbe Health Toronto, an urban Aboriginal community health centre, addresses the specific healthcare needs of the urban population through a multidisciplinary culturally appropriate healthcare model. As my research evolved, a few themes emerged from the data. First, the health issues experienced by the clientele were inherently complex and simultaneously infused with a culturally collective and individualistic quality. Second, practitioners acknowledged and addressed the complex nature of the clients’ health problems through a unique model of health care created at the centre. Third, the philosophy, infrastructure, and model of health care at Anishnawbe Health Toronto goes beyond the notion of merely offering access to both systems of health care, and instead constitutes an innovative and culturally appropriate system of care which is under Aboriginal control, development and implementation. Therefore, through my analysis of these themes, I conclude that the model of health care developed at the centre is an example of complex solutions designed to address complex Aboriginal health issues and as a result, facilitate the embodiment of self-determination in the area of health care.
Keywords: Aboriginal Health; Traditional Healing; Culturally Appropriate Care; Medical Pluralism; Self Determination; Social and Cultural Anthropology; Social and Cultural Anthropology